THE EFFECT OF LEADERSHIP, JOB SATISFACTION, ORGANIZATIONAL CITIZENSHIP BEHAVIOUR AND COMPETENCE ON EMPLOYEE PERFORMANCE (CASE STUDY AT XYZ MINISTRY IN INDONESIA) - Tri Rejeki, Rini; Mei Nur Widigdo, Aslam (Dinasti Publisher, 2021)
This research has purpose to discover the affect of leadership, job satisfaction, organizational citizenship behavior, and competence on employee performance in XYZ Ministry. The research method used quantitative approach with the type of research is included in causal research. The research population was 1,587 permanent employees at Work Units and Technical Implementation Units of XYZ Ministry in Jabodetabek. The sampling technique was proportional stratified random sampling with the number of samples was 94 employees. These research data were obtained by distributing questionnaires. The quantitative data analysis method uses multiple linear regression methods. The results showed if 1) Leadership partially has the strongest and significant impact on employee performance. 2) Job satisfaction partially has a significant impact on employee performance. 3) Organizational citizenship behavior partially has a significant impact on employee performance. 4) Employee competence partially has a significant impact on employee performance. 5) Leadership, job satisfaction, organizational citizenship behavior and employee competence simultaneously have a significant impact on employee performance.